VD_FINDINFO Jug / 2011 / 225 vom 6. Oktober 2011 - VD Tribunal cantonal (2011)
EXCÈS, LÉGITIME DÉFENSE, EXCITATION, DÉPENS | 16 al. 2 CP, 398 al. 4 CPP (CH), 429 al. 1 let. a CPP (CH), 429 al. 2 CPP (CH)